Smart Power Systems and Renewable Energy System Integration - Jayaweera, Dilan; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This monograph presents a wider spectrum of researches, developments, and case specific studies in the area of smart power systems and integration of renewable energy systems. The book will be for the benefit of a wider audience including researchers, postgraduate students, practicing engineers, academics, and regulatory policy makers. It covers a wide range of topics from fundamentals, and modelling and simulation aspects of traditional and smart power systems to grid integration of renewables; Micro Grids; challenges in planning and operation of a smart power system; risks, security, and stability in smart operation of a power system; and applied research in energy storage. .
Fundamentals of Power Systems -- Modelling and Simulation of Power Systems -- Micro Grid Planning and Operation -- A study on Conversion Efficiency Improvement of Multi-Junction PV Cells with MPPT -- Grid Integration of Renewable Energy Systems- Technical Challenges, Security and Risk in Grid Integration of Renewable Energy -- Dynamic Modelling, Simulation and Control of a Commercial Building Micro Grid -- Probabilistic Methods Applied in Power and Smart Grids -- Planning and Operational Challenges in a Smart Grid -- Applied Research in Energy Storage.
Keywords: Control engineering; Electric power production; Energy storage; Renewable energy sources; Control and Systems Theory; Electrical Power Engineering; Mechanical Power Engineering; Mechanical and Thermal Energy Storage; Renewable Energy